Optimizing Supply Chain Network Design Under Uncertainty: A Practical Methodology for Sustainable Value Creation - Mili , Khaled (Journal of Ecohumanism, 2024)
Evaluating supply chain network (SCN) designs is critical for organizations striving to optimize operations and achieve sustainable value creation. However, conventional models often oversimplify, failing to account for the complexities inherent in real-world supply chain environments. In this study, we propose an advanced approach to SCN evaluation that strikes a balance between practicality and sophistication, leveraging real-world data to inform decision-making. Our methodology aims to bridge the gap between theoretical models and practical implementation, offering a pathway to sustainable value creation in SCN design. By incorporating risk analysis, resilience modeling, and solution methods tailored to uncertainty, our approach provides a comprehensive framework for addressing the challenges of SCN design under uncertainty. Simulation results validate the efficacy of our methodology in facilitating informed decision-making and strategic planning within organizations.